Ecopedagogy and Sangserekan: Relational Foundations for the Integrity of Creation in Contemporary Christian Education - Yosia Geby (Fakultas Keguruan dan Ilmu Pendidikan Kristen IAKN Palangka Raya, 2026)
This article examines the relationship between ecopedagogy and the concept of sangserekan as a relational foundation that supports the integrity of creation within contemporary Christian education. Ecopedagogy is understood as an educational approach that encourages critical awareness of ecological crises, the development of ethical responsibility, and the formation of transformative practices that nurture just relationships between humans and the environment. Sangserekan, a local wisdom tradition emphasizing reciprocity, cooperation, and communal interconnectedness, offers significant potential to enrich theological reflection and pedagogical practice within Christian settings. Through a review of relevant literature and theological–pedagogical reflection, this article proposes the integration of these two perspectives to create a framework that emphasizes not only cognitive learning but also character formation, ecological spirituality, and relational consciousness. This integrated approach can help learners understand their vocation as stewards of creation, cultivate solidarity with others and the natural world, and build stronger commitments to sustainability. Thus, ecopedagogy and sangserekan provide a relevant and contextually grounded relational foundation for churches and Christian educational institutions seeking to address global ecological challenges and promote just and sustainable learning practices.